Solidarity outpatient clinics in Greece: a survey of a massive social movement - Iro Evlampidou; Manolis Kogevinas (Elsevier, 2019)
Objective: Until 2016, around 3 million persons had limited access to health care in Greece due to the economic crisis. We describe a massive solidarity movement of community clinics and pharmacies in Greece. Method: We conducted a survey in 2014-15 and describe the characteristics of community clinics and pharmacies spontaneously established all over Greece after 2008. Results: A characteristic of the 92 active solidarity clinics is autonomous collective functioning, free services, and funding from non-governmental sources. The largest clinics examined more than 500 uninsured or partly insured patients per month. Clinics covered a wide range of clinical and preventive services. Funding, availability of drugs, vaccines, medical material and their legal status were the main problems identified. The solidarity movement involved thousands of health professionals covering essential population needs. Conclusions: The community outpatient clinics were an outstanding example of solidarity and temporarily alleviated the health needs of a large part of the population. Resumen: Objetivo: Hasta 2016, alrededor de 3 millones de personas tenían acceso limitado a la atención médica en Grecia debido a la crisis económica. Describimos un movimiento masivo de solidaridad de clínicas comunitarias y farmacias en Grecia. Métodos: Realizamos una encuesta en 2014-15 y describimos las características de las clínicas comunitarias y de las farmacias espontáneamente establecidas en toda Grecia después de 2008. Resultados: Una característica de las 92 clínicas solidarias activas es el funcionamiento colectivo autónomo, con servicios gratuitos y financiación de fuentes no gubernamentales. Las clínicas más grandes examinaron más de 500 pacientes no asegurados o parcialmente asegurados por mes. Las clínicas cubrieron una amplia gama de servicios clínicos y preventivos. La financiación, la disponibilidad de medicamentos, vacunas y material médico, y su estado legal, son los principales problemas identificados. El movimiento de solidaridad involucró a miles de profesionales de la salud que cubrieron las necesidades esenciales de la población. Conclusiones: Las clínicas ambulatorias comunitarias fueron un ejemplo de solidaridad y aliviaron temporalmente las necesidades de salud de una gran parte de la población. Keywords: Economic recession, Greece, Health policy, Delivery of health care, Palabras clave: Recesión económica, Grecia, Políticas de salud, Prestación de asistencia sanitaria